Reduction Kinetics Of Dusts And Pellets From Nickeliferous Laterite Rotary Kiln Treatment - Emmanuel N. Zevgolis Ismene-Polyxeni Kostika (The Minerals, Metals and Materials Society, 2005)
Keywords: reduction, kinetics, laterites, rotary kiln, dust In this work, the reduction kinetics of dust from nickeliferous Greek laterites is investigated. The dust is a by-product from laterite treatment in rotary kilns and it comes from washing towers, electrostatic filters and polycyclones. Laboratory made pellets from this dust were also examined. Reducibility was studied in the temperature range of 700°C to 850°C in a laboratory tube furnace. Kinetic analysis of the results showed that at lower temperature values the mixed kinetic model verifies the experimental results of dust and pellet samples. At higher temperatures (800° and 850°C) diffusion becomes the rate controlling mechanism. The calculated activation energy values verify also the above mentioned results.